Elevated urinary monocyte chemoattractant protein-1 levels in children with Henoch-Schonlein purpura nephritis - Jiapei Wang; Qianqian Ying; Shiling Zhong; Yuanling Chen; Yazhen Di; Xiahua Dai; Jika Zheng; Mengjiao Shen (Pediatrics and Neonatology)
Chemokine monocyte chemoattractant protein-1 (MCP-1) has been proved as a potential urinary biomarker in nephropathies. The aim of this study was to investigate the urinary monocyte chemoattractant protein-1 (MCP-1) levels and clinical significance in Henoch-Schonlein purpura (HSP) children with and without nephritis and determine the association of MCP-1 with proteinuria. Methods: A total of 261 HSP children—with or without nephritis—and 84 healthy control children were enrolled in this study. Of these, 126 HSP nephritis (HSPN) children were subdivided into three groups according to total urine protein in 24 h (TUP): Group A, mild proteinuria group with TUP <25 mg/kg; Group B, moderate proteinuria group with TUP ≥25 mg/kg and <50 mg/kg; Group C, severe proteinuria group with TUP ≥50 mg/kg. Urinary MCP-1 levels were determined by ELISA. Levels of serum creatinine (Cr), blood urea nitrogen (BUN), urinary α1-micro globulin (α1-MG), micro-albumin (mAlb), immunoglobulin G (IgG), transferrin (TRF) and TUP were performed to determine their associations with MCP-1. Results: Urinary MCP-1 was significantly higher in HSPN group in comparison with HSP group and controls (P < 0.05), but no significant difference was found between the HSP group and the healthy group (P > 0.05). The levels of urinary MCP-1 increased in parallel to the enhancement of total urine protein in 24 h in HSPN patients. There were statistically significant differences among these three groups of HSPN children (p < 0.05). Urinary MCP-1 correlated positively with urinary α1-MG, mAlb, IgG, TRF and TUP in HSPN, whereas no correlation was observed with serum Cr and BUN. Conclusions: MCP-1 was elevated in children with HSPN and correlated with proteinuria. Urinary MCP-1 could be used as a suitable, non-invasive biomarker to provide valuable information not only for the diagnosis of HSPN, but also for evaluation of severity of renal damage.